Stedelijk Museum Amsterdam in 2001. - Bouwhuis, Jelle; Fuchs, Rudi H.; Van Beek, Willem; van Adrichem, Jan; van Heusden, Stevijn; Stedelijk Museum Amsterdam (Amsterdam : Stedelijk Museum Amsterdam, 2002)
Aalto, Alvar ; Olde Wölbers, Saskia ; Hopper, Dennis ; Colton, Adam ; Malevich, Kasimir ; Vanderheyden, JCJ ; Hanzlová, Jitka ; Sarcevic, Bojan ; Appel, Karel ; Villevoye, Roy ; Picasso, Pablo ; Vrankic, Davor ; de Jong, Folkert ; Tuttle, Richard ; Zandvliet, Robert ; Birza, Rob ; Scheffer, Frank ; Basilico, Gabriele ; Dubuffet, Jean ; Tan, Fiona ; Nauman, Bruce ; Charlton, Alan ; Verhoef, Toon ; Sieverding, Katharina ; Nouwens, Monica ; Kirchner, Ernst Ludwig ; Rockenschaub, Gerwald ; Houseago, Thomas ; Kraijer, Juul ; Caris, Gerard ; Scheibitz, Thomas ; van Lieshout, Erik ; Schouten, Marien ; Gygi, Fabrice ; van Hout, Seet ; Newman, Barnett ; Preesman, Avery ; Rudelius, Julika ; Wessing, Koen ; Sandberg, Willem ; Goossens, Marnix ; Poncelet, Jacqui ; Francis, Sam ; Lichtenstein, Roy ; de Kooning, Willem ; Rauschenberg, Robert ; Kelly, Ellsworth ; Rothko, Mark
Engels
Nederlands
boek